1997
DOI: 10.1002/(sici)1096-9861(19970602)382:2<176::aid-cne3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-immunoreactivity in peripheral tissues of the opisthobranch molluscsPleurobranchaea californicaandTritonia diomedea

Abstract: The distribution of serotonin (5-HT)-immunoreactive elements in peripheral organs of the sea-slugs Pleurobranchaea californica and Tritonia diomedea was studied in cryostat sections. For Pleurobranchaea, 5-HT-immunoreactive (5-HT-IR) neuron cell bodies were found only in the central nervous system (CNS); 5-HT-IR cell bodies were not observed in foot, tentacles, rhinophores, oral veil, mouth, buccal mass, esophagus, gills, salivary glands, skin, reproductive system, and acidic glands, nor in peripheral tentacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 49 publications
6
46
1
Order By: Relevance
“…Neurotransmitters such as acetylcholine, dopamine and serotonin (5-HT), diverse neuropeptides such as substance P and calcitonin gene-related peptide have been identified (3,6,7). There is some disagreement regarding the presence of monoaminergic or peptidergic neuronal somata in the foot (8).…”
Section: Introductionsupporting
confidence: 62%
“…Neurotransmitters such as acetylcholine, dopamine and serotonin (5-HT), diverse neuropeptides such as substance P and calcitonin gene-related peptide have been identified (3,6,7). There is some disagreement regarding the presence of monoaminergic or peptidergic neuronal somata in the foot (8).…”
Section: Introductionsupporting
confidence: 62%
“…We presume that branchlets of LOVN and TN coinnervate some of the ganglia. Inhibitory interactions among sensory afferents or interneurons could take place in the small glomerular, ganglion-like structures associated with the sensory afferents or in the nearby subepithelial meshworks associated with sensory epithelium (Moroz et al 1997). More exact details of synaptic interconnections in the oral veil demand a greatly more detailed study of anatomy and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…051007) in PBS with 0.2% Triton X-100 and 2% NGS overnight at room temperature. This antibody was used successfully in previous studies in gastropod molluscs (Croll et al 2003;Moroz et al 1997;Wertz et al 2006). After Wve rinses in PBS, sections were incubated in Alexa Fluor 488-conjugated goat anti-rabbit secondary antibody (1:250, Molecular Probes, Eugene, OR, USA, Cat.…”
Section: Methodsmentioning
confidence: 95%
“…In A. punctata, the rhinophore ganglion and the glomeruli are innervated by centrifugal serotonergic processes (Wertz et al 2006). Similar to results in the opisthobranchia Pleurobranchaea and Tritonia (Moroz et al 1997) and sensory organs in Phestilla, serotonergic cell bodies were shown to be absent in the periphery (Croll et al 2003).…”
Section: Introductionmentioning
confidence: 93%